2003
DOI: 10.1073/pnas.2628040100
|View full text |Cite
|
Sign up to set email alerts
|

Autonomous T cell trafficking examined in vivo with intravital two-photon microscopy

Abstract: The recirculation of T cells between the blood and secondary lymphoid organs requires that T cells are motile and sensitive to tissue-specific signals. T cell motility has been studied in vitro, but the migratory behavior of individual T cells in vivo has remained enigmatic. Here, using intravital two-photon laser microscopy, we imaged the locomotion and trafficking of naïve CD4 ؉ T cells in the inguinal lymph nodes of anesthetized mice. Intravital recordings deep within the lymph node showed T cells flowing r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

35
456
5

Year Published

2003
2003
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 461 publications
(496 citation statements)
references
References 42 publications
35
456
5
Order By: Relevance
“…From these experiments, the locations of individual T cells moving in lymphoid organs are obtained as a function of time (5)(6)(7)(8). The instantaneous and mean velocities of T cells, their mean free paths, and their trajectories in the presence and the absence of Ag-presenting dendritic cells can thus be determined.…”
Section: Ovement Of T Cells Within Lymphoid Organs Facilitatesmentioning
confidence: 99%
“…From these experiments, the locations of individual T cells moving in lymphoid organs are obtained as a function of time (5)(6)(7)(8). The instantaneous and mean velocities of T cells, their mean free paths, and their trajectories in the presence and the absence of Ag-presenting dendritic cells can thus be determined.…”
Section: Ovement Of T Cells Within Lymphoid Organs Facilitatesmentioning
confidence: 99%
“…Moreover, since the mice are unharmed during the imaging process, it might be possible to perform longitudinal studies on individual research subjects. The first report of intravital 2P being used to study lymphoid tissues appeared in 2003 [11] and since then several variations of this approach have been widely adopted to study lymphocytes and antigen presenting cells in vivo [12]. This technique has changed our static view of the immune system and provided a tantalizing glimpse of the complex cellular dynamics that underlie the immune response [13].…”
Section: Introductionmentioning
confidence: 99%
“…Since the uveitis model employed for this study involves the introduction of a foreign antigen and the use of a TLR 4 agonist, LPS, the APCs should be stimulated and are presumably elaborating chemokines that attract T cells. Mean displacement plots (MDPs) are commonly employed as a method to determine if cell movement is random, directed, or confined as by a structure such as a vessel or a collagen bundle [26]. The MDPs in Figure 3 include data from 42 DO11.10 T cells in the irises of seven mice that had been injected with ovalbumin and in 24 DO11.10 T cells in the irises of ten control mice injected with BSA.…”
Section: Resultsmentioning
confidence: 99%
“…Lymphocytes with the T cell zone of a lymph node also follow paths that have been classified as analogous to random walks by mean displacement plots [26]. More recently it has been shown that the vast majority of lymph node T cells actively follow along fibers of the fibroblastic reticular cell network.…”
Section: Discussionmentioning
confidence: 99%